2015
DOI: 10.1371/journal.pone.0122369
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Multidrug Resistance IncF Plasmid from the Globally Disseminated Escherichia coli ST131 Clone

Abstract: Escherichia coli sequence type 131 (E. coli ST131) is a recently emerged and globally disseminated multidrug resistant clone associated with urinary tract and bloodstream infections. Plasmids represent a major vehicle for the carriage of antibiotic resistance genes in E. coli ST131. In this study, we determined the complete sequence and performed a comprehensive annotation of pEC958, an IncF plasmid from the E. coli ST131 reference strain EC958. Plasmid pEC958 is 135.6 kb in size, harbours two replicons (RepFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 87 publications
4
54
0
Order By: Relevance
“…Our result supports the view that the IncF (both FI and FII) family was well adapted and commonly distributed in E. coli and Salmonella (14, 15, 34, 46). Wang et al (14) reported that IncFIIA was detected only in S. enterica serotype Typhimurium, which correlates with our findings; however, we also detected the FIIA type in the S. enterica serotype 4,12:i:Ϫ. IncF family plasmids have been reported to contribute to the spread of AMR in Enterobacteriaceae and have been associated with specific genes conferring resistance to aminoglycosides, ␤-lactams, and quinolones (43,46,47).…”
Section: Figsupporting
confidence: 90%
“…Our result supports the view that the IncF (both FI and FII) family was well adapted and commonly distributed in E. coli and Salmonella (14, 15, 34, 46). Wang et al (14) reported that IncFIIA was detected only in S. enterica serotype Typhimurium, which correlates with our findings; however, we also detected the FIIA type in the S. enterica serotype 4,12:i:Ϫ. IncF family plasmids have been reported to contribute to the spread of AMR in Enterobacteriaceae and have been associated with specific genes conferring resistance to aminoglycosides, ␤-lactams, and quinolones (43,46,47).…”
Section: Figsupporting
confidence: 90%
“…We previously found that a plasmid resembling pEC958 and harboring FIA and FII (16) was present in approximately 80% of the ESBL- E. coli ST131 isolates from Nepal (5). The high prevalence of IncF (IncFIA, FIB, and FII) observed among ESBL- E. coli ST131 isolates from Nepal is consistent with these previous reports and is reasonable considering the high prevalence of H 30Rx among ESBL- E. coli ST131 isolates.…”
Section: Resultsmentioning
confidence: 99%
“…The LysR family transcriptional regulator lrhA has previously been shown to repress both fimB and fimE (Blumer et al ., ), and our identification of lrhA in this study as a repressor of fimE is consistent with these results. The yubO gene is located on a 135.6 kb IncF plasmid in EC958 and encodes a protein of unknown function (Phan et al ., ). Three independent Tn 5 mutants were identified in yubO , however specific mutagenesis of yubO failed to reproduce a significant increase in fimE transcription (data not shown).…”
Section: Discussionmentioning
confidence: 97%